Hearing aid trial periods: Audiologists' thoughts and practices in South Africa. - Angie Heliopoulos; Nomfundo Moroe (Public Library of Science (PLoS), 2023)
The process of adjusting and becoming accustomed to hearing aids may be best facilitated by providing a hearing aid trial period. Globally, there are no standardised frameworks or regulations on the recommended hearing aid trial period. The main purpose of this study was to explore audiologists' hearing aid trialing practices. A cross sectional study employed a quantitative, descriptive design to formulate the study. Ninety-five audiologists' were recruited by means of a purposive sampling strategy. Data were collected through the use of an online survey via Google forms. A pilot study was conducted prior to the commencement of the main study in order to ensure reliability of the main study. The results indicated that two weeks was the most recommended duration of a trial period from audiologists'. Majority of audiologists' (72.63%) offer hearing aid trials to their patients. Most audiologists' who offer hearing aid trials choose to trial their patients with two different hearing aids. Findings revealed a need for trialing periods to become standard practice by audiologists' when fitting hearing aids. Not enough audiologists' are providing this service.